(untitled) (Albayan Scientific Journal, 2023)
A total of 54 strains of Escherichia coli isolated from mid stream urine samples of urinary tract infection patients attending Tobruk medical center . The strains sensitivity to antimicrobial drugs were tested. High incidence of resistant strains, high degree of association between resistance , most strains were resistance to one or more antibiotics. And several patterns of antibiotics resistance occurred. E. coli showed very resistant to Amoxicillin+Clavulonic acid (68.5%). Sulfamethoxazol+ Trimethoprim (62.96%). And moderately resistant to Chloramphenicol (22.22%). Meropenem (20.37%). Amikacin(18.51%). However it was low resistant to Gentamicin, Ciprofloxacin and Levofloxacin (16.66%) of each one.